Gangguan pada Sistem Urinaria dan Pengobatan Herbal: Sebuah Studi Meta-Analisis - Afriani, Arikah Putri; Rachmadani, Fairuz Najla; Saputra, Rifky Adi; Rusdi; Rahayu, Sri (Politeknik Baubau, 2024)
Urinary tract infection is a type of infection that occurs in one or all organs in the urinary system and is generally caused by bacterial infections, one of which is Klebsiella pneumonia. Treatment of urinary tract infections is carried out by administering antibiotics, however, this method actually increases the incidence of antibiotic resistance. Therefore, alternative treatments are needed to replace the antibiotics used for urinary tract infections. This is a meta-analysis study that aims to obtain information about alternative treatments for urinary tract infections using herbal medicines and their mechanisms. This research begins with a search for relevant references, then selecting the articles that are truly relevant with the topic, and extracting the data. The data used was secondary data extracted from the references, then statistically tested with Ancova t-test and effect size calculation. The extraction results showed that the usage of herbal plant extracts was able to provide an inhibitory zone on the growth of Klebsiella pneumonia, which indicates that herbal plant extracts are able to provide antipathogenic effects for Klebsiella pneumonia. The Ancova t-test results showed a sig. value is 0.000 which indicates that there is a clear and significant effect of the herbal plants extract as an anti-uropathogen of Klebsiella pneumonia. The calculation of effect size also showed a value is 0.882 which means that the herbal plants used as an anti-uropathogen of Klebsiella pneumonia has a very large effect.